الشخصية الصباحية - المسائية وعلاقتها بإدمان الإنترنت لدى طلاب الجامعة - علام، سارة مهدي سعد (جامعة كفر الشيخ - كلية التربية, 2016)
The present study aims to: •Study and understand the nature of the relationship between personal morning - evening and Internet addiction. •Study the differences between personal patterns morning and evening in the personal Internet addiction. •Identify the differences between Internet addicts, male and female in the personal morning - evening. The sample included basic study on 100 students from undergraduate students, of which (50), male, and (50) of the female, age group (18-21 years.) The researcher used the following tools: •Personal Scale morning - evening preparation (researcher.) •Internet Addiction Scale (IAS) preparation (human Ismail Ahmed 0.2013.) The study found the following results: •no statistically significant correlation between the personal morning - evening and Internet addiction. •There are significant differences between those with morning and evening personal profile and those with Internet addiction in the personal benefit of the evening. •There are no significant differences between males and females with personal evening in Internet addiction.
تهدف الدراسة الحالية إلى ما يلي: -دراسة وفهم طبيعة العلاقة بين الشخصية الصباحية – المسائية وإدمان الإنترنت. -دراسة الفروق بين أنماط الشخصية الصباحية والشخصية المسائية في إدمان الإنترنت. -التعرف على الفروق بين مدمني الإنترنت من الذكور والإناث في الشخصية الصباحية-المسائية. واشتملت عينة الدراسة الأساسية على (100) طالبا وطالبة من طلاب المرحلة الجامعية، بواقع (50)، من الذكور، و (50) من الإناث والفئة العمرية (18- 21) سنة. واستخدمت الباحثة الأدوات التالية: -مقياس الشخصية الصباحية – المسائية إعداد (الباحثة). -مقياس إدمان الأنترنت (IAS) إعداد (بشري إسماعيل أحمد، 2013). وتوصلت الدراسة إلى النتائج التالية: -توجد علاقة ارتباطية ذات دلالة إحصائية بين الشخصية الصباحية – المسائية وإدمان الإنترنت. -توجد فروق ذات دلالة إحصائية بين ذوي الشخصية الصباحية وذوي الشخصية المسائية في إدمان الإنترنت لصالح الشخصية المسائية. -لا توجد فروق ذات دلالة إحصائية بين الذكور والإناث من ذوي الشخصية المسائية في إدمان الأنترنت.
Keywords: السياسة التعليمية -- البرامج التعليمية -- الوسائل التعليمية -- طرق التدريس -- المهارات التعليمية -- الشخصية الصباحية -- الشخصية المسائية -- وسائل الإتصالات -- الإنترنت -- الإدمان -- التعليم الجامعي -- طلبة الجامعات -- مستخلصات الأبحاث